Early childhood caries intervention in Aboriginal Australian children: Follow-up at child age 9 years - Xiangqun Ju; Joanne Hedges; Dandara Gabriela Haag; Gustavo Hermes Soares; Lisa Gaye Smithers; Lisa M. Jamieson (PLoS ONE, 2025)
Objective Dental caries is one of the most common preventable diseases among Indigenous children. The study aimed to estimate the efficacy of an Early Childhood Caries (ECC) intervention among Aboriginal Australian children over 9 years, and to explore potential risk factors associated with dental caries among Indigenous Australian children. Methods Data were from a randomized controlled trial conducted in South Australia, Australia. Four hundred and forty-eight women pregnant with an Aboriginal child were randomly allocated to either an immediate (II) or delayed (DI) intervention group between January 2011 and May 2012. The immediate intervention comprised (1) provision of dental care to mothers during pregnancy; (2) application of fluoride varnish to teeth of children at ages 6, 12; and 18 months; (3) motivational interviewing delivered in conjunction with; and (4) anticipatory guidance. Mothers/children in the DI group received the same intervention commencing at child aged 2 years. Follow-ups occurred when children were aged 2-, 3-, 5-, 7- and 9-years. In this analysis, outcomes were severity of caries experience: mean dmft/DMFT at child aged 9 years. Dependent variables included mothers’ baseline and seven years follow-up characteristics (age, education level, source of income, residential location, smoking and alcohol status) and children’s birth and feeding, and dental behaviours characteristics (sex, gestation, birth weight, breastfeeding status and sweet food consumption, and frequency of tooth brushing). Multivariable log-Poisson regression models with robust standard error estimation were applied as a statistical model to estimate multivariable relationships of dental caries and other covariates. Risk ratios (RRs) with their 95%CI were calculated. Sensitivity analyses were conducted by using the inverse-probability-of censoring weighting (IPCW) to overcome the loss-follow-up issues. Results Data were available for 367 (II = 180 and DI = 187) children at age 9 years. The mean dmft was 3.41 (95% CI: 2.95–3.87) and DMFT was 0.31(95%CI: 0.22–0.41). In multivariable modelling, mean dmft was higher (RR = 1.13, 95% CI: 1.01–1.26) among DI children than II children, but there were no significant differences in the permanent dentition. Risk factors for caries severity in both the primary and permanent dentition included lower mothers’ education level (<12 years level: dmft; RR = 1.56, 95% CI:1.31–1.86; and ‘Trade or TAFT: DMFT: RR =3.40, 95%CI: 1.16-9.98). Other risk factors for dental caries experience in the primary dentition included preterm birth, low birth weight, child not breastfed and sugar consumption more than 10%, and in permanent dentition was self-rated ‘fair/poor’ or ‘Good’ children’s oral health, compared with self-rated ‘Excellent/very good’ oral health. Conclusion The present study suggests that, within this cohort, initiating an early childhood caries intervention during pregnancy and infancy may be associated with lower caries experience in the primary dentition by age 9 years compared to a later start. Low maternal education level was associated with caries severity in both primary and permanent dentitions. Sugar consumption, a modifiable risk factor, greater than 10% was an important contributor to dental caries in primary teeth.